Identifikasi Penguasaan Konsep Materi Hukum Archimedes dan Hukum Pascal Berbantuan Quizizz - Faradila Nur Anjelin; Fatmatul Ailiyah; Bakhrul Rizky Kurniawan; Mimin Nurul Kholifah (Universitas Islam Negeri Maulana Malik Ibrahim Malang)
This article aims to reveal the mastery of concepts activated by respondents when answering questions related to Pascal's law and Archimedes law. This study used a survey method with a test instrument of 10 multiple choice questions on the topic of static fluids using Quizizz. The subjects used to research were physics students from semester 6 to high school students who had received static fluid material. The research was conducted online with a period of 10 days and obtained 34 respondents. The data analysis techniques used were quantitative and qualitative analysis with 51% of the results obtained showed that students were still low in mastering the concept of Pascal's law and Archimedes' law.